Towards Digital Bangladesh: Scope of ICT integrated Urban Planning and Management - Kabir, Mohammad Rasel (Journal of Bangladesh Institute of Planners, 2012)
The world has already entered into the Information Age where information regulates all types of activities. Developed countries have gained expertise dealing with the information in their decision support systems for planning, governing, service delivery and management of resources. With the “internet bust” of the last few years, ICT becomes an enormous engine of the development process. Bangladesh and other developing countries are yet to attain this technological benefit. At present, the Government of Bangladesh (GoB) is striving to turn the country into “Digital Bangladesh” by launching an ICT based planned development and management practices throughout the country. Optimum utilization and management of the resources through better planning and management of the facilities, improve the life standard of the city dwellers. ICT can ensure the best utilization of existing resources and ease the management process. In addition to that, ICT can generate virtual spaces for delivering services and creating employment opportunities, and thus can go over the limitation of physical spaces. The current trend in development indicates that the local government institutions will be the major hub of information communication in near future, albeit the easy storage, retrieval, analysis and integration of the spatial data with non-spatial datasets requiring involvement of various central and local government institutions/departments simultaneously. A conceptual guideline is provided here for the professionals engaged in urban planning and management in the country about the changing circumstances in information based planning practices. This paper mainly examines the dimension and prospect of E-planning in Bangladesh and depicts the role of different stakeholders in this process. The ways in which urban planning and management practices may best be altered in this regard is also addressed. Journal of Bangladesh Institute of Planners, Vol. 5, Dec 2012, pp. 169-183